COMPLICATIONS AND FAILURES IN MODERN IMPLANTOLOGY - Spoiala (Budaca); Paiu Raluca-Georgiana; Yildiz Yasemine; Vasiliu Lacramioara; Istrati Ionela; Forna Norina Consuela (Romanian Dental Association for Education, 2022)
Aim of the study:The aims of this study are to review the available literature related to implant complications and propose a new classification method for dental implant complications and describe different methods and treatment modalitiesto deal with dental implant failure. Material and methods: Dental literature was reviewed via focusing on articles and published in English, which included data regarding dental implants and complications. Data from 106 patients with 186 dental implants were analyzed. The presence of sucessful healing (yes/no) at the time of incorporation of the final prosthesis was assessed. Mixed models were compiled for each target variable to enable estimation of the effects of patient-related andimplant-related conditions on the risk of early implant failure. Results:Types of complications in these three groups (Mild, Moderate, and Severe) were listed, and some of them were illustrated. Also, recommendations for clinicians were made on how to avoid these problems and/or overcome them. Nine out of 186 implants (4.8%) placed in 106 participants failed before incorporation of the final prosthesis.The use of shorter implants (< 10mm) and the need for augmentation procedures were associated with a greater risk of early implant failure. For shorter implants, the risk was 5.8 times greater than that for longer implants (p = 0.0230). Use of augmentation procedures increased the risk by a factor of 5.5 (p = 0.0174). Conclusions:Implants placed in the dental practice with a specialization in implantology heal successfully. The use of augmentation procedures and of implants shorter than 10mm seems to be associated with a greater risk of early implant failure.The ultimate success of implants is not only based on diagnosis, evaluation, treatment planning but also on having a knowledge regarding the complications of implants and their fruitful management. In short it is always better to remember: 'Prevention is better than cure' and 'a stitch in time saves nine.'